Persepsi Generasi Milenial Terhadap Kualitas Pelayanan Tracking System pada Jasa Pengiriman JNE - Hadi, Abdul; Resista Vikaliana (ARBITRASE: Journal of Economics and Accounting, 2023)
One of the freight forwarding or logistics service companies that utilizes it is PT Titipan Kilat Jalur Nugraha Ekakurir (JNE). Not only about service, logistics companies must also pay attention to the timeliness of delivery of goods that are carried out, delivery time is the period of time the customer orders the product until it arrives in the hands of the consumer himself. The research aims to determine the effect of the quality of the tracking system service on JNE delivery services on the satisfaction of the millennial generation in Bekasi Regency and to study the effect of service quality on JNE delivery services on the satisfaction of the millennial generation in Bekasi Regency. Data collection was carried out using questionnaires, observation and library research. While the data collected was analyzed by validity test, reliability test, normality test, simple linear regression test, correlation coefficient test, coefficient of determination test and hypothesis test T. The results of the research conducted were the perception of the millennial generation on the variable perception of the service tracking system that provide experience to know the position of the goods is very good. It can be seen from the value obtained, which is 4.22 with a very good interpretation. The attitude of the JNE courier on the perception variable also shows a good value of 4.13 with a good interpretation. The quality of service at JNE is still lacking, as can be seen from the indicator of the facilities provided by JNE with a value of 3.57, although the interpretation is good, it still needs to be improved so that it is better than its competitors.